Associations of social capital resources and experiences of homophobia with HIV transmission risk behavior and HIV care continuum among men who have sex with men in Los Angeles. Issue 5 (4th May 2021) - Takada, Sae; Gorbach, Pamina; Brookmeyer, Ron; Shoptaw, Steve
ABSTRACT: For men who have sex with men (MSM) in the US, the positive and negative aspects of social capital – access to resources within their social networks and experiences of homophobia – may explain their disproportionate burden of HIV infection. We analyzed data from 379 HIV seronegative and seropositive MSM in Los Angeles, collected between May 2017 and February 2018. Dependent variables were HIV transmission risk behaviors and care continuum outcomes. We used multivariable logistic regression to estimate the association between social capital resources and experiences of homophobia with dependent variables, adjusting for sociodemographics and drug use. Most participants were under age 40 and 41% identified as Black/African American and 36% as Hispanic/Latino. Social capital resources associated with likelihood of new sexually transmitted infections (−5.5% per standard deviation (SD), 95%CI −10.3, 0.7%) and HIV testing (5% per SD, 95%CI 0.8, 9.2%). Experiences of homophobia associated with likelihood of methamphetamine use during sex (10% per SD, 95%CI 7, 14%), receiving (4.3% per SD, 95%CI 1.9, 6.7%) and giving (7.2% per SD, 95%CI 4.5, 9.9%) exchange sex, and missing appointments (7.2% per SD, 95%CI 0.8, 13.6%). Findings that social capital associated with HIV transmission risk behaviors and HIV testing suggest interventions to increase social capital resources would impact the HIV-prevention continuum.